Thermo-electric effects in a Luttinger liquid - Krive, I.V.; Romanovsky, I.A.; Bogachek, E.N.; Scherbakov, A.G.; Landman, Uzi (Физика низких температур, 2001)
Thermoelectric effects in a Luttinger liquid (LL) wire